Menciptkan Kepuasan Kerja Melalui Lingkungan Kerja dan Komunikasi Interpersonal pada PT.Temas Tbk - Cynthia Caroline; Joseph M.J. Renwarin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of work environment and interpersonal communication on employee job satisfaction at PT. Temastbk. There are three variables in this study which include the work environment, interpersonal communication and employee job satisfaction. This study uses quantitative methods by calculating the distribution of questionnaires using paper questionnaires as its distribution to 62 respondents who are employees of PT. Temas Tbk. Sampling in this study, using a saturated sample which is part of non-probability sampling and data analysis used using the SPSS 13 application. The results show that the work environment variable has a significant influence on employee job satisfaction, while interpersonal communication has a significant influence on employee job satisfaction. Simultaneously, these two variables have a significant effect on the employee job satisfaction variable. Keywords: work environment, interpersonal communication, job satisfaction